2019
DOI: 10.1002/jppr.1464
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative doctor–pharmacist prescribing in the emergency department and admissions unit: a study of accuracy and safety

Abstract: Prescribing by pharmacists in a collaborative manner has been occurring in the UK for several years. There are minimal studies involving pharmacist prescribing in Australia. In the present audit, 34 medication charts (17 each from the pharmacist prescriber and medical officer) were reviewed for safety and accuracy. Medication charts written by a pharmacist were more accurate than those written by a medical officer when compared to the medication history. Discrepancies and omissions had more potential for patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…These studies included 13 242 participants in total, with sample sizes varying considerably between 34 and 3594 participants 17 18. Ten studies were controlled pre–post interventional studies,19–28 nine were cohort studies,29–37 three were RCTs,38–40 three were controlled concurrent studies,18 41 42 three were pre–post interventional studies without controls,17 43 44 two were controlled sequential studies45 46 and one was a multicentre cross-sectional study 47. Seven of the studies exclusively limited the participants to older adults, aged 65 years and above 18 23 28 40 41 45 46…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies included 13 242 participants in total, with sample sizes varying considerably between 34 and 3594 participants 17 18. Ten studies were controlled pre–post interventional studies,19–28 nine were cohort studies,29–37 three were RCTs,38–40 three were controlled concurrent studies,18 41 42 three were pre–post interventional studies without controls,17 43 44 two were controlled sequential studies45 46 and one was a multicentre cross-sectional study 47. Seven of the studies exclusively limited the participants to older adults, aged 65 years and above 18 23 28 40 41 45 46…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were controlled pre–post interventional studies,19–28 nine were cohort studies,29–37 three were RCTs,38–40 three were controlled concurrent studies,18 41 42 three were pre–post interventional studies without controls,17 43 44 two were controlled sequential studies45 46 and one was a multicentre cross-sectional study 47. Seven of the studies exclusively limited the participants to older adults, aged 65 years and above 18 23 28 40 41 45 46…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent Australian studies have demonstrated partnered pharmacist charting of medicines to be safe and effective in reducing medication‐related errors in areas such as orthopaedics, the emergency department and general medicine . Partnered pharmacist anticoagulant prescribing in an Australian ambulatory care Hospital In The Home (HITH) program, reduced time to reach therapeutic INR and facilitated earlier discharge back to community care …”
Section: Introductionmentioning
confidence: 99%
“…This extends the scope by offering additional flexibility to pharmacists prescribing beyond "Supplementary prescribing" which is limited to working in partnership with an independent prescriber within an individualised clinical management plan (206). Pharmacist-Physician Collaborative Ordering of Medications on admission and discharge is a model of care with proven benefits in medication safety and appropriateness, continuity of care, reduced length LOS and has been demonstrated to be sustainable (76,196,201,(207)(208)(209). As presented and discussed in Chapter four, 8.3% of in-depth discussions were not actioned in the comparator group and 7.1% in the intervention group: these offer an opportunity for improved prescribing.…”
Section: The Ptwr Pharmacist As a Prescribermentioning
confidence: 99%